2010
DOI: 10.18269/jpmipa.v15i2.283
|View full text |Cite
|
Sign up to set email alerts
|

Kontribusi Asesmen Formatif Terhadap Habits of Mind Mahasiswa Biologi

Abstract: Study about formative assessment contribution to habits of mind of the Biology students purposes to describe weather there is a formative assessment contribution (feedback, self assessment and peer assessment) to the forming of student habits of mind. The research was carried out in Biology Education Departement to students who took Botany Phanerogamae instruction on 2009/2010. Many of formative assessment strategies were applied on theory and practical study, such as group presentation task, concept diagram, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 2 publications
1
10
0
8
Order By: Relevance
“…In situations where an individual does not know how to respond to a problem, it is necessary to behave intelligently to overcome it in the sense of not only knowing the information but also knowing how to act. The ability to behave intelligently is referred to as habits of mind (Sriyati, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In situations where an individual does not know how to respond to a problem, it is necessary to behave intelligently to overcome it in the sense of not only knowing the information but also knowing how to act. The ability to behave intelligently is referred to as habits of mind (Sriyati, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several previous studies have discussed how RME influences learning (Atika & Mz, 2016;Dolk & Eerde, 2013;Hidayat & Iksan, 2015;Rudiono, Dafik, & Wahyuningrum, 2015), research in improving mathematical analogical abilities (Azmi, 2017;Rahman & Maarif, 2014), and research examining habits of mind (HOM). (Bidari, 2016;Indriani, 2018;Masni, 2017;Miliyawati, 2017;Nahadi, H, & Farina, 2015;Nurmaulita, 2014;Sriyati, Rustaman, & Zainul, 2010;Zhok, 2016). However, there has been no research that investigates the effect of RME learning in improving mathematical analogical abilities and habits of mind (HOM).…”
Section: Introductionmentioning
confidence: 99%
“…A number of research from Sriyati claimed that habits of mind was self-regulation in learning and found a solution in social relations in the workplace. (Sriyati, Rustaman, & Zainul, 2010).…”
Section: Student's Mathematical Problem Solvingmentioning
confidence: 99%
“…Instrumen yang digunakan dalam penelitian ini adalah rubrik HoM. Rubrik penelusuran HoM diadopsi dan dikembangkan dari Marzano (2006) dan Sriyati (2011). Rubrik ini terdiri dari beberapa pertanyaan yang tediri dari tiga kategori regulasi diri, berfikir kreatif dan berfikir kritis.…”
Section: Metode Penelitianunclassified